ADAPTASI DAN KERAGAAN HASIL PADI VARIETAS INPARA DI LAHAN RAWA - Koesrini Koesrini (Research Center for Biology-Indonesian Institute of Sciences, 2018)
Inpara is a rice variety rice released by the Indonesian Agency for Agricultural Research and Development (IAARD) which is adaptive to swamp land. The research objective was to evaluate the adaptability and yield performanceof Inpara varieties in swamp lands. The field experiment was conducted in tidal swamp lands, in Barito Kuala District and in swampy lands, Hulu Sungai Selatan District of South Kalimantan, during dry season of 2014. The research was arranged in a randomized complete design with three replications. The treatment was 7 Inpara varieties, i.e. Inpara 1, 2, 3, 4, 5, 6, 7 and comparison varieties, i.e Margasari in tidal swamp lands and Ciherang in swampy lands. The result showed that there was a variation adaptation between Inpara varieties in tidal swamp land and swampy lands. Inpara 2 and Inpara 3 varieties showed a good adaptation in tidal swamp lands, had the yield of 4.04 t/ha which an increasing yield was 35.9% higher than Margasari variety. Inpara 1 and Inpara 6 varieties presented a good adaptation in swampy lands that produced 2.118 t/ha and 2.275 t/ha and 1.9% and 9.5%, respectively higher than Ciherang variety. Variety of Inpara is not adaptive in swamp lands.